The Translation Shift in The Translation of The English Recount Text Into Indonesian at SMP Swasta Ben’s Group Buntu Bayu Hatonduhan - Manurung, Novita Gresiana; Siahaan, Sanggam; Purba, Christian Neni (Universitas Pahlawan Tuanku Tambusai, 2024)
This research was intended to find out types of translation shift in category shift according to J.Catford of students in translating recount text from English into Indonesia at SMP Swasta Ben's Group Buntu Bayu Hatonduhan. Therefore, the researcher formulated a question as the problem. As follows: “What are the translation shift used in translating recount text from English into Indonesian?